Cross-national comparison of dynamic inefficiency for European dietetic food manufacturing firms - Kapelko, Magdalena; Harasym, Joanna; Orkusz, Agnieszka; Piwowar, Arkadiusz (Technological and Economic Development of Economy, 2022)
Food health and wellness has become increasingly important for consumers, and this has inevitably caused growth in the dietetic food manufacturing sector. This paper examines the technical inefficiency of dietetic food manufacturing firms in five major dietetic food producing European countries (France, Italy, Norway, Poland and Spain) for the period 2009–2017. To account for the sluggish adjustment of capital, we employed a dynamic production framework within the nonparametric method of Data Envelopment Analysis. Furthermore, we used the concept of a metafrontier to compare inefficiency between countries and analyzed three inefficiency measures: estimated with regard to a metafrontier (pooled dynamic inefficiency), computed with reference to country-specific frontier (managerial dynamic inefficiency), and the gap between these two frontier measures (program dynamic inefficiency). The results indicate that firms in Poland were the least dynamically inefficient among countries analyzed, while companies in Norway were at the opposite end of the spectrum. Managerial inefficiency was the largest source of pooled inefficiency for firms in France and Italy, while program inefficiency was the main reason of pooled inefficiency for firms in Norway, Poland and Spain. The results also reveal that investments were the most inefficient factor, followed by output, materials and employees. First published online 25 April 2022